Effects of palonosetron and dexamethasone on postoperative nausea and vomiting in adult patients undergoing laparoscopic abdominal surgery: a randomized, double-blind, clinical trial at a tertiary care hospital - Tahir, Sifna; Mir, Altaf Ahmad; Hameed, Abdul (International Journal of Advances in Medicine, 2016)
Background: Post-operative nausea and vomiting (PONV) is one of the common problems after laparoscopic abdominal surgery. It hampers the postoperative recovery in spite of the availability of many antiemetic drugs and regimens for its prevention. We evaluated the effectiveness of intravenous (IV) palonosetron in counteracting PONV during the first 48hrs following laparoscopic abdominal surgery, using dexamethasone as the comparator drug. Methods: In this study a single pre-induction IV doses of palonosetron (75mcg) or dexamethasone (8mg) were administered to adult patients of either sex undergoing elective laparoscopic abdominal surgery. There were 40 subjects per group. The pre-anesthetic regimen, anesthesia procedure and laparoscopic technique were uniform. The primary effectiveness measure was total number of PONV episodes in the 48 hours period following end of surgery. The frequencies of individual nausea, retching and vomiting episodes, visual analog scale (VAS) score for nausea at 2, 6, 12, 24 and 48 hours, use of rescue antiemetic (metoclopramide), number of complete responders (no PONV or use of rescue in 48 hours) and adverse events were secondary measures. SPSS software version 16 was employed to using student’s t-test, chi-square test or fisher’s exact tests. Value of P < 0.05 was considered significant. Results: The incidence of nausea and vomiting was maximal during the first six hours postoperatively. The complete control of postoperative nausea and vomiting for first 24 hours was achieved in 80% patients of palonosetron group and 60% patients of dexamethasone group. During 24-48 hours the incidence of PONV was 17.5% and 22.5% respectively in palonosetron group and dexamethasone group. The use of rescue medication is about 50% less in the use of palonosetron as antiemetic than dexamethasone. Safety profile was similar in both the groups. Conclusions: Palonosetron is comparatively highly effective to prevent the PONV after anaesthesia in elective laparoscopic abdominal surgery when administered as single pre-induction dose due to its prolonged duration of action than dexamethasone.